Observasi Penerapan Kurikulum Merdeka Belajar di SMAN 1 Sedayu Kabupaten Bantul - Afroni Nur Faizin; Dody Tri Iwandana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Education is something that cannot be separated from human life. Thanks to education, humans gain knowledge. In order for educational goals to be achieved, it requires effort and support from various educational components that are interconnected and influence each other. One of them is the curriculum. The Free Learning Curriculum is one way to respond to educational challenges that have arisen as a result of the post-pandemic education crisis. The Free Learning Curriculum that emerged to deal with educational problems during this endemic period formulated several new policies that offered freedom for schools and students in carrying out learning. The purpose of this research is to find out whether the Independent Learning Curriculum has been implemented or not. In this study, researchers used qualitative research methods that aim to explain the phenomenon in depth and is achieved by collecting data in detail. The steps taken with data collection techniques are by interviewing teachers as research subjects, then documenting the research data related to them. As a result, the Free Learning Curriculum has not been implemented, there are still obstacles that cause the Free Learning Curriculum to be implemented at SMAN 1 Sedayu. Keyword : Penerapan, Kurikulum Merdeka Belajar